The Duality of the MAPK Signaling Pathway in the Control of Metabolic Processes and Cellulase Production in Trichoderma reesei - Renato Graciano de Paula (Nature Portfolio, 2018)
Abstract In this study, through global transcriptional analysis by RNA-Sequencing, we identified the main changes in gene expression that occurred in two functional mutants of the MAPK genes tmk1 and tmk2 in Trichoderma reesei during sugarcane bagasse degradation. We found that the proteins encoded by these genes regulated independent processes, sometimes in a cross-talk manner, to modulate gene expression in T. reesei. In the Δtmk2 strain, growth in sugarcane bagasse modulated the expression of genes involved in carbohydrate metabolism, cell growth and development, and G-protein-coupled receptor-mediated cell signaling. On the other hand, deletion of tmk1 led to decreased expression of the major genes for cellulases and xylanases. Furthermore, TMK1 found to be involved in the regulation of the expression of major facilitator superfamily transporters. Our results revealed that the MAPK signaling pathway in T. reesei regulates many important processes that allow the fungus to recognize, transport, and metabolize different carbon sources during plant cell wall degradation.